Adam Smith and Rousseau ethics, politics, economics - Paganelli, Maria Pia 1972-; Rasmussen, Dennis C. 1978-; Smith, Craig 1977- (Edinburgh studies in Scottish philosophy, 2018)
This collection brings together an international and interdisciplinary group of Adam Smith and Jean-Jacques Rousseau scholars to explore the key shared concerns of these two great thinkers in politics, philosophy, economics, history and literature